O Programa Institucional de Bolsa de Iniciacao à Docencia (PIBID): as repercussões na perspectiva de seus atores - Maria de Lourdes Ribeiro Gaspar (2017)
This thesis focus on the Institutional Program of Initiation to Teaching (PIBID) and emphasizes the actions developed under this program in the Federal Institution of the North of Minas Gerais and Triângulo Mineiro, specifically in the Biological Sciences courses, from subprojects developed by these two institutions. The research sought to analyze the process of recontextualization of PIBID by the participants involved - Grant Recipients of Initiation to Teaching (ID), Teachers Supervisors (SUP) and Area Coordinators (CA). Furthermore, the research attempted to identify how the speeches that guide the PIBID are unique in each institution. Firstly, issues related to teacher education, as well as to policies in this area, were discussed, based on the literature that deals with these fields. Next, the implementation of PIBID was analyzed based on a brief survey on the region where the two institutions are located and a data survey that made it possible to outline the participants profile. The central point of this thesis is to identify and analyze how the legal provisions and the guiding documents that regulate the Institutional Program of Initiation to Teaching are interpreted in the speeches of the participants of this program. The research used as a methodological procedure, the documentary analysis, the questionnaire and the semi-structured interview. During the first step, questionnaires with closed questions were applied, the data was processed through the SPSS software, and the data was then used to generate guiding axes of the interviews performed with ID, SUP and CA. The Bardin Content Analysis was used to evaluate the interview data (2009). The results indicate that the PIBID, in fact, favored the inclusion of future teachers in the education system, however, the program was not able to overcome the distance between the higher education system and the basic education system, since the former behaves like the one that holds the theory, and the second, the practice. It was also found that the PIBID favored a rethinking process about the practices used by the area coordinator teachers, although it did not manage to modify the formative actions within the licentiate course, since they are confined to changes in the teaching practice only of those involved with the program. Additionally, it was verified that the insertion of the grant recipient of ID in the basic education system causes changes in the perception of the future teacher about teaching methods and the perspectives of the graduate student on the profession, guiding the graduate student to a postgraduate program and reinforcing in the student the desire to become a professor. Lastly, the research highlights, that experiences such as the PIBID show that even achieving some of its objectives, broader and more radical measures are critical for effective changes in initial training and undergraduate courses. These measures include career enhancement, which can be obtained by increasing teacher salaries and improving working conditions of teachers, as well as changes in the curriculum of initial training courses of future professionals, among others. Finally, it can be said that only within a new professional scenario will it be possible to draw up a national policy of effective and profitable teacher education.